2016
DOI: 10.3892/ol.2016.4595
|View full text |Cite
|
Sign up to set email alerts
|

Isolated port-site metastasis after surgical staging for low-risk endometrioid endometrial cancer: A case report

Abstract: Abstract. Port-site metastases (PSMs) are well-known potential complications of laparoscopic surgery for gynaecologic malignancies. The present case study reports PSM following laparoscopic surgery for Stage IA Grade 1 endometrioid endometrial cancer (EEC). The recurrence developed within 7 months following primary surgery and required surgical excision followed by adjuvant chemo-radio therapy. After 9 months, the patient remains disease-free. PSMs are rare complications following laparoscopic surgery. Amongst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 41 Early endometrial cancer patients (Stage IA Grade 1) can also develop PSM after laparoscopic surgery. 42 However, most cases have shown that PSM tends to occur in advanced cancer, and patients at risk for recurrence may have a poor prognosis because of their advanced cancer status. However, this theory may not apply to early-stage ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 Early endometrial cancer patients (Stage IA Grade 1) can also develop PSM after laparoscopic surgery. 42 However, most cases have shown that PSM tends to occur in advanced cancer, and patients at risk for recurrence may have a poor prognosis because of their advanced cancer status. However, this theory may not apply to early-stage ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The overall incidence of PSM in gynecologic malignancies has been reported to be 1-2%. [7][8][9] For primary gynecologic tumors with surgical indications, primary surgery is important, and thorough surgery is closely related to patient survival. However, the surgical indications vary among different types of gynecologic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…25 Reports of surgically-induced seeding in malignancies like, wound metastasis in open surgery and port site metastasis in laparoscopic surgery are becoming an emerging problem for surgeons. 26 However, "benign metastasis" is also possible as evidenced by endometriosis seen in ectopic locations. 27 One interesting report is the development of ameloblastoma on the iliac bone donor site which can only be explained by tumor contamination during the graft harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pattern of recurrence, concerns were raised for the hypothetic risk of augmented frequency of vaginal cuff recurrence and the possible localization at the port site [91]. In the analysis conducted in 2012 on recurrence and OS in patients enrolled in the LAP2 study, no statistically significant difference was found in vaginal recurrence between laparoscopy and laparotomy [27].…”
Section: Cervical Cancer 476mentioning
confidence: 99%